2021
DOI: 10.1371/journal.pone.0256964
|View full text |Cite
|
Sign up to set email alerts
|

Cross-pollination affects fruit colour, acidity, firmness and shelf life of self-compatible strawberry

Abstract: Cross-pollination affects the fruit characteristics of many crops but the effects of cross-pollination on fruit quality of strawberry (Fragaria × ananassa Duch.) are poorly known. This study determined how cross-pollination affects fruit quality of the strawberry cultivar, Redlands Joy, under controlled environment conditions. Plants were allocated to one of four treatments, with all flowers on each plant receiving either: (1) unassisted self-pollination (Autogamy); (2) hand-pollination with Redlands Joy polle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
1
12
0
1
Order By: Relevance
“…Fruit size is possibly regulated by the amount of water uptake, which may be affected by sugar concentrations as sugar contributes significantly to osmotic strength and water uptake. We have shown in our two previous studies that cross-pollinated ripe fruit often have higher Brix:acid ratio, but not higher Brix, than self-pollinated fruit [ 15 , 16 ]. However, sugar levels in the young developing fruit require further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fruit size is possibly regulated by the amount of water uptake, which may be affected by sugar concentrations as sugar contributes significantly to osmotic strength and water uptake. We have shown in our two previous studies that cross-pollinated ripe fruit often have higher Brix:acid ratio, but not higher Brix, than self-pollinated fruit [ 15 , 16 ]. However, sugar levels in the young developing fruit require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Xenia effects on blueberry, strawberry and pear fruit size [ 17 19 , 34 ] were evaluated when self-pollinated fruit and cross-pollinated fruit developed on different plants. We have recently demonstrated that xenia effects on the size of mature fruit of self-compatible Redlands Joy do not occur when self-pollinated and cross-pollinated develop on different plants [ 15 ]. However, xenia effects on mature fruit size become apparent when self-pollinated and cross-pollinated fruit compete on the same Redlands Joy plant [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations